THE INFLUENCE OF EDUCATION, TRAINING AND COMPETENCE ON PERFORMANCE THROUGH WORK MOTIVATION IN VILLAGE DEVICES SEBINTAN DISTRICT - Mawarni, Mawarni; Eleonora Rumengan, Angelina; Indrayani, Indrayani; Khaddafi, Muammar (RADJA PUBLIKA, 2023)
Education, training and competence of employees are needed to deal with changes that occur such as changes in technology, changes in work methods in village development. The purpose of this study was to analyze the influence of education, training and competency on performance through work motivation in Village Officials throughout Bintan Regency, totaling 324 Village Officials. The population in this study amounted to 179 Village Officials in Bintan Regency. In this study, the sampling technique used was nonprobability sampling with the technique taken, namely saturated sampling (census). The research method uses an associative method with a quantitative approach to the analysis of Partial Least Square (PLS) analysis techniques with the SmartPLS program. The results of the research variable on education have a positive and significant effect on work motivation and performance. Training has a positive and significant effect on work motivation. Training has no significant effect on performance. Competence has a positive and significant effect on work motivation, while competence has no significant effect on performance and work motivation has a positive and significant effect on performance. The indirect test of work motivation is an intervening variable between education, training and competency on performance. while competence has no significant effect on performance and work motivation has a positive and significant effect on performance. The indirect test of work motivation is an intervening variable between education, training and competency on performance. while competence has no significant effect on performance and work motivation has a positive and significant effect on performance. The indirect test of work motivation is an intervening variable between education, training and competency on performance.